A gênese e o desenvolvimento do programa de extensão - AFRID - da Faculdade de Educação Física da Universidade Federal de Uberlândia: de 1989 a 2014 - Medeiros, Izaura de Menezes (2017)
This work is the result of a master’s research carried out in the Post-Graduation Program in Education of the Federal University of Uberlândia, in the History and Historiography of Education line. It is inserted in the field of studies of higher education and more specifically, presents the history of the university, through a university extension action, called Recreational and Physical Activities for the Elderly (AFRID), object of this research. The temporal cut goes from 1989, when the project was created, until 2014, the year of its 25th year of uninterrupted operation, with the purpose of highlighting the context of its creation and implementation as an extension action at the Faculty of Physical Education (FAEFI), in the Federal University of Uberlândia (UFU). As theoretical foundation, Antônio Gramsci's historical legacy sought the conception of organic intellectual, having as its axis of analysis the philosophy of praxis. This study is of a qualitative nature, using documentary and oral sources, crossing the data from these sources in the construction of the history of AFRID and the university extension in UFU. Preceding to this, an extensive research was done in databases to know about the subject of extension, and bibliographic research on the history of extension, history of UFU and AFRID, as well as the policies that promoted extension in Brazilian universities, comparing to know and to reflect on the conceptions of extension that foment doing it in the AFRID and UFU. Notably, the extension in Brazilian universities, and therefore in UFU also, gained expression as an academic, scientific and cultural process, after the creation of FORPROEX - National Forum of Extension Pro-Rectors - in 1987, however, it is from the publication of the National Extension Plan by the MEC in 1999, that extension begins to occupy the academic space in a more organized and conceptually based way, highlighting itself as a transforming social reality, even in slow steps. The extension, while social and political practice also goes through several stages during the period studied in the AFRID, being the work developed, strongly influenced in how the UFU systematized its extension. The AFRID over 25 years of extension work has developed numerous projects benefited the elderly and collaborated with student training, promoting an extension that makes you think proposing solutions and, above all, causes the dissolution of old welfare paradigms, providing also, the observation that extension is the education of countless possibilities, and the indissociability between teaching-research-extension is possible, collaborating in the construction of new ideas and meanings for university extension.